1969
DOI: 10.1136/gut.10.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gastrectomy on biliary dynamics.

Abstract: A recent study of the physiology of flow through the sphincter of Oddi (Wyatt, 1967) indicated that amongst other factors gastric peristalsis was related to changes of resistance at the sphincter. This was especially notable when food was present in the stomach. Electrical stimuli leading to contraction of the gastric antrum often resulted in relaxation of the sphincter with increased flow through it. This relationship did not depend on extrinsic nervous connexions and was therefore supposed to depend on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Early work by Wyatt (1967Wyatt ( , 1969 showed that gastric peristaltic contractions decreased the SO perfusion resistance and a Polya type of gastrectomy ceased this coordination but did not cause biliary hypertension reflecting an increase in the SO resistance in the dog. Although the coordination of the gastric contraction and the SO motility was not observed in the present experiment, the perfusion pressure of the SO, an indicator of its resistance, and the frequency of phasic contractions of the SO increased significantly after gastrectomy (from the level at the gastric and gastroepiploic vessel to the uppermost duodenum), but not after sham-gasterctomy or vagosympathectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Early work by Wyatt (1967Wyatt ( , 1969 showed that gastric peristaltic contractions decreased the SO perfusion resistance and a Polya type of gastrectomy ceased this coordination but did not cause biliary hypertension reflecting an increase in the SO resistance in the dog. Although the coordination of the gastric contraction and the SO motility was not observed in the present experiment, the perfusion pressure of the SO, an indicator of its resistance, and the frequency of phasic contractions of the SO increased significantly after gastrectomy (from the level at the gastric and gastroepiploic vessel to the uppermost duodenum), but not after sham-gasterctomy or vagosympathectomy.…”
Section: Discussionmentioning
confidence: 99%
“…To further complicate our understanding of SO activity, the SO has distinct regions and intra‐sphincteric reflexes may exist between these regions 11,51,52 . In addition, SO activity is also modulated by neural reflexes that exist between the SO and the stomach, 53,54 the duodenum, 14,37,40,55,56 and the CBD/gallbladder 57–59 . Of these reflexes, the most extensively studied is the duodenal‐SO reflex.…”
Section: Neural Reflexes Between the So And Other Organsmentioning
confidence: 99%
“…The object of this review was to see whether, in fact, ulcer surgery might be a significant aetiological factor in cholelithiasis. Johnson andBoyden (1952), Cox et al (1958), and Tinker and Cox (1969) noted alterations of gall-bladder physiology after vagotomy, and Wyatt (1969) noted changes after partial gastrectomy. After vagotomy there is an increased gall-bladder volume with increased emptying rate, the gall bladder becoming supersensitive to cholecystokinin.…”
Section: Commentmentioning
confidence: 99%